2019
DOI: 10.1001/jamanetworkopen.2019.0348
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Machine Learning vs Standard Prediction Rules for Predicting Hospital Readmissions

Abstract: This prognostic study compares standard readmission risk assessment scores with a machine learning score, the Baltimore score, for predicting 30-day unplanned hospital readmissions calculated in real time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 13 publications
2
55
0
2
Order By: Relevance
“…Moreover, the current study found only a portion of variables have predictive power for readmission among home care patients (one out four variables in the LACE index, three out of six variables in the HOSPITAL score, respectively). Therefore, some studies suggested introducing more variables or using state-of-the-art methods such as machine learning and deep learning to gain a better predictive power [39][40][41]. However, using the real-world data, we found that both the LACE index and HOSPITAL score models already perform far better than physicians and might be good enough in readmission rate reduction for home care patients.…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, the current study found only a portion of variables have predictive power for readmission among home care patients (one out four variables in the LACE index, three out of six variables in the HOSPITAL score, respectively). Therefore, some studies suggested introducing more variables or using state-of-the-art methods such as machine learning and deep learning to gain a better predictive power [39][40][41]. However, using the real-world data, we found that both the LACE index and HOSPITAL score models already perform far better than physicians and might be good enough in readmission rate reduction for home care patients.…”
Section: Discussionmentioning
confidence: 79%
“…[18][19][20][21][22][23][24][25][26] Although many studies have concluded that AI-based models are superior to traditional models for risk stratification, other studies have observed otherwise. 14,[27][28][29][30][31][32][33][34][35][36][37][38][39] While clinical factors have primarily been used to predict readmission, there has also been interest in incorporating sociodemographic factors into models to more accurately account for patients' sociopersonal contexts, which are increasingly recognized to affect health-related outcomes. [10][11][12][13]40 This is critical because health behaviors, social factors, and economic factors are estimated to account for 70% of a person's health.…”
Section: Predictive Analytics For Hospital Readmissionmentioning
confidence: 99%
“…Standard methods to predict hospital readmission typically rely on a limited set of clinical data using simple calculations such as a modified LACE score that exams at the length of hospital stay, acuity on admission, comorbidity and emergency department visits. 6 When comparing standard methods to ML, some researchers found that ML scores were better at predicting hospital readmissions. 6 However, others showed mixed results, 7 highlighting the need for further research to clarify discrepancies in predictive models.…”
Section: Introductionmentioning
confidence: 99%
“…6 When comparing standard methods to ML, some researchers found that ML scores were better at predicting hospital readmissions. 6 However, others showed mixed results, 7 highlighting the need for further research to clarify discrepancies in predictive models.…”
Section: Introductionmentioning
confidence: 99%